A Study of Nitrate Uptake from Aqueous Solutions Using Isotactic Polypropylene-based Anion Exchangers - Banyal, Sunil K.; Chauhan, Ghanshyam S.; Sharma, Rajiv K. (Journal of Membrane and Separation Technology, 2013)
Two series of efficient and cost-effective anion exchangers possessing biocidal properties are reported for the removal of nitrate ions from aqueous solutions. Isotactic polypropylene (IPP) was modified by graft copolymerization with poly(4-vinyl pyridine) using γ-rays as initiator. The graft copolymers were functionalized further by reaction with sodium 2-bromoethane sulphonate or 2-Chloroethanol to generate, respectively, the zwitterionic or choline-analogous structure on the IPP backbone. The functionalized graft copolymers have exchangeable Cl- or Br- ions and possess antimicrobial properties due to their polycationic character. These exhibited structure-property relationship when evaluated as anion exchangers for NO3- ions of which the maximum was removed from the feed solution with the graft copolymer having the lowest percent grafting. But the nature of the counter anion present did not exhibit much difference in the nitrate uptake behaviour. A parametric study, to evaluate the effect of different conditions on nitrate uptake, was carried as a function of contact time, temperature, pH of medium and NO3- concentration. A high maximum exchange capacity of 14.77 mg/g and 13.62 mg/g was observed, respectively for the graft copolymers having Br- and Cl- as the counter anions, at pH 5.0, 35 ºC, and 20 ppm of the nitrate ions after ten cycles. The materials also exhibited good reusability up to ten cycles. The kinetics and mechanism of nitrate removal was studied and the data was found to fit the pseudo-second order kinetics and Langmuir isotherm.